FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR TAHUN 2017-2019 - Christian Alessandro; Augustpaosa Nariman (Jurnal Paradigma Akuntansi, 2022)
This research aims to find out how the role of the firm's size, profitability and liquidity to the company's capital structure, especially in manufacturing companies listed on the Indonesia Stock Exchange during 2017-2019. Sample selection was done by purposive sampling method and valid data obtained are 76 companies. Data processing techniquesusing multiple regression analysis assisted by EViews data processing software version 11 and Microsoft Excel 2019. The results of this study show that the size of the firm has a significant influence on the company's capital structure, and that profitability and liquidity have an influence on the company's capital structure. The implication of this research isthat the company's management can optimize the capital structure of the company to maintain the continuity of its company.